Strategi Pengembangan SDM: Upaya Penunjang Daya Saing UMKM di Era Pandemi Covid 19 - Imran Ukkas; Muhammad Kasran (Program Studi Manajemen Fakultas Ekonomi Universitas Samudra, 2023)
Human Resource development for SMEs needs to be carried out in order to improve SMEs competitiveness in the Covid 19 pandemic era. This study aims to discover an effective formulation of Human Resource quality development strategies for SMEs in Palopo as an effort to support SMEs competitiveness in the Covid 19 pandemic era. The Methods used is descriptive qualitative with SWOT analysis. The results show that the position on the IE Matrix diagram is in quadrant IV which means it is in a Grow and Build condition. Meanwhile, in the SWOT matrix, it is in quadrant I, which means that the right strategy is carried out, which is an aggressive strategy. Alternative strategies which can be done include increasing Human Resource skills in mastering digital technology in supporting business development.